65. Transcranial magnetic stimulation in refractory NCSE: Personal experience and future studies. Issue 4 (April 2016) - Monti, F.; Stragapede, L.; Furlanis, G.; Mantovan, L.; Romano, G.
Abstract : The use of repetitive TMS (rTMS) for epilepsy is a potential therapy. In literature several case reports were published with different results. We describe two cases of refractory focal NCSE treated with rTMS with different stimulus parameters. During rTMS we monitored the brain electrical activity with standard EEG, according with our previously experiences in EEG/TMS co-registration. The stimulus was applied over the epileptic focus, according with EEG registration. We used a train stimulus of 0.5 or 1 Hz at 70 or 100 % of motor threshold, for 20 min. In the first case rTMS decreased suddenly the electrical paroxysm. In the second case rTMS reduced, but not abolished, the ictal activity. We think that the use of rTMS in selected refractory cases of both convulsive and non-convulsive status epilepticus can be useful when conventional therapies have failed. In addition, in these cases the EEG/TMS coregistration is mandatory. Future studies should investigate various rTMS parameters in different patients with refractory focal status epilepicus.